Test of plant defense elicitors for arthropod pest suppression and PR‐1 gene induction in pear orchards. Issue 12 (9th October 2021) - Orpet, Robert J.; Cooper, W. Rodney; Beers, Elizabeth H.; Nottingham, Louis B.
Abstract: Plant defense elicitors (PDEs) are chemicals that stimulate plant defenses against pathogens and herbivores. Previous work shows that PDEs acibenzolar‐S‐methyl (ASM) and harpinαβ protein (harpin) can induce the pathogenesis‐related gene PR‐1 in plants and suppress herbivorous arthropods. In this study, we tested the potential for these PDEs to induce PR‐1 in pear, Pyrus communis L. (Rosaceae) orchards and suppress pear psylla, Cacopsylla pyricola (Förster) (Hemiptera: Psyllidae), and spider mites, Tetranychus spp. (Acari: Tetranychidae). In 2017, we compared densities of each pest on mature pear trees following a single application of either an ASM product (Actigard; Syngenta), a harpin product (Employ; Plant Health Care), or no PDE treatment in four commercial and two research center orchards. In 2018, we sampled pear psylla and used qPCR to assess PR‐1 induction in pear leaf samples before and after PDE treatments at one commercial orchard. Neither PDE treatment showed evidence of pest suppression in either year, and no differences in PR‐1 expression were detected. Potted greenhouse trees treated with ASM in 2019 showed higher PR‐1 expression relative to untreated trees, verifying that our procedures can detect induction and suggesting that a single PDE application was sufficient to induce PR‐1 in potted but not mature pear trees. We conclude that plant defense elicitors may contribute to pear pest suppression in some contexts, but effects are unlikely to be strong or consistent. Our results highlight the need for field experiments to advance plant defense elicitor knowledge towards effective field applications. Abstract : We tested potential for two plant defense elicitors (PDEs), acibenzolar‐S‐methyl and harpinαβ protein, to suppress the pests pear psylla, Cacopsylla pyricola (Hemiptera: Psyllidae), and spider mites, Tetranychus spp. (Acari: Tetranychidae), in multiple pear orchards. The plant pathogenesis‐related gene PR‐1 was induced in treated potted pear trees but not in mature orchard trees, which did not have reduced pest densities compared with controls. Effects of PDEs under realistic conditions need more study to develop them into effective management tools against herbivores.